PENGARUH MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMA - Ritzi Anggita; Tian Abdul Aziz; Esti Ambar Nugraheni (Universitas Muhammadiyah Bengkulu, 2019)
This research aims to examine the results from the effectiveness of the Student Facilitator and Explaining (SFaE) the learning model on students' mathematical communication skills at one of the private schools in Tangerang city in the 2018/2019 academic year with the topic of sequences and series. In this research the method used a Quasi Experimental with research designs The Nonequivalent Pretest-Posttest Control Group Design. This study uses classes that are already available. The research sample used is clas XI MIPA 1 as many as 35 students as the experimental class and class XI MIPA 3 as many as 35 students as the control class. Data is collected from the result of the pretest and posttest mathematical communication skills that student work with the number of valid questions that 15 of 20 questions. Data were analyzed using a two-party test. Based on this research of this study states that the Student Facilitator and Explaining (SFaE) learning model effects the mathematical communication ability of students at SMA one of the private schools in Tangerang city which obtained a mean score of 26,97 with a standard deviasi of 5,576 with a significance level of 0,05 and obtained the influence of 0,656 which includes moderate interpretations.Keywords : Student Facilitator and Explaining, Mathematical Communication